GSTM1/GSTT1 double-null genotype increases risk of treatment-resistant schizophrenia: A genetic association study in Brazilian patients - Pinheiro, Denise S.; Santos, Rodrigo da S.; de Brito, Rodrigo B.; Cruz, Aline Helena da S.; Ghedini, Paulo C.; Reis, Angela A. S. (PloS one, 2017)
The role of oxidative stress in schizophrenia has been demonstrated, particularly in subjects with treatment-resistant schizophrenia (TRS). In such patients, the decreased levels of antioxidants in conjunction with the increased generation of reactive oxygen species in the brain exposes the neurons to a higher risk of damage. We evaluated the association of deletion polymorphisms of two genes of the antioxidant Glutathione S-Transferase family, GSTT1 and GSTM1, with susceptibility to TRS. A total of 54 TRS patients (mean age 38.7 years) and 78 healthy control subjects (mean age 39.0 years) were enrolled in this study. The subjects were matched by sex, age, and smoking and alcohol consumption habits. In the case group, the frequencies of GSTT1-null and GSTM1-null genotypes were 24.1 and 51.9%, respectively, whereas for the control group, the frequencies were 12.8 and 46.2%, respectively. Analysis performed with respect to the risk of developing TRS associated with the GSTT1 and GSTM1 deletion polymorphisms, resulted in odds ratio (OR) values of 2.1 and 1.2, respectively. However, the association was not found to be significant (p = 0.1229 and p = 0.5916, respectively). The analysis performed with respect to the combined genotypes of GSTT1 and GSTM1 revealed that the double-null genotype confers a 4.6-fold increased risk of developing TRS (p = 0.0412). The results of the present study indicate that a combination of GST deficiencies may play a role in enhanced susceptibility to TRS, and the present genotype of one of these genes may buffer the deficiency caused by the lack (null genotype) of the other. The results suggest that combined deletion polymorphisms of GSTT1 and GSTM1 can have implications in the prediction of the clinical course of the disease.